ЕРТЕК ТИП СЮЖЕТЛИ ДӘСТАНЛАРДЫҢ ҲӘМ ЕРТЕКЛЕРДИҢ ОБРАЗЛАР СИСТЕМАСЫНЫҢ ӨЗ-АРА УЛЫЎМАЛЫҚ ТӘРЕПЛЕРИ («Шарьяр» дәстаны мысалында) - Кеңесбаева, Ш.К. (FAN va JAMIYAT, 2022)
The article examines the aspects of epics with a fairy-tale plot related to fairy tales. Basically, the commonality in the system of images is studied and analyzed on the example of Shahriyor’s epic.